Hormonal Influence on Mood Dysregulation: A Case of Bipolar Disorder with Endometriosis - Sakdyah, Halimatus; Septina, Egy Atthahirah; Pramesta, Linda Ramadhanty; Ikhsan, Muhammad; Shafira , Alsa; Nurhayati , Endi; Algristian, Hafid (Yayasan Sinergi Kawula Muda, 2025)
Bipolar disorder often coexists with gynecological conditions such as endometriosis, presenting clinical challenges due to overlapping hormonal and neuropsychiatric influences. The impact of hormonal therapy on mood stability in women with affective disorders remains underexplored. We report the case of a 30-year-old woman with bipolar II disorder, stable for nearly two years on lamotrigine, who developed mood destabilization after initiating hormonal treatment for stage III endometriosis. Sequential regimens—dienogest, norethisterone, and ethinylestradiol–levonorgestrel—were temporally associated with new or worsening mixed affective symptoms, including agitation, insomnia, irritability, and emotional lability, despite adherence to mood stabilizers. Her Hamilton Depression Rating Scale score increased from 9 to 21 within three months, with laboratory evaluation showing elevated estradiol and suppressed luteinizing hormone, supporting a hormone-related mechanism. A structured literature review (PubMed, Scopus, Google Scholar, 2000–2024) identified limited but consistent evidence that synthetic progestins may exacerbate psychiatric symptoms in mood-vulnerable populations through neuroendocrine and neurotransmitter modulation. This case underscores the importance of recognizing hormonally induced mood dysregulation in women with pre-existing psychiatric disorders and highlights the need for proactive management strategies. We recommend pre-treatment psychiatric screening, structured and longitudinal mood monitoring throughout hormonal therapy, and close interdisciplinary collaboration between gynecology and psychiatry to optimize outcomes. Integrated care approaches may reduce the risk of mood destabilization, enhance safety, and improve quality of life for women facing the dual burden of bipolar disorder and endometriosis.